Strategic advantage analysis of a leading low cost carrier in Thailand : a case of Thai AirAsia and NokAir - Punjarod Toppoopha (Chulalongkorn University, 2019)
In this study, the author focus on an objective that is why Thai AirAsia can generate different levels of net profits from NokAir even two airlines are under similar environmental conditions and began business operations in a close year. Hence, the Author examined their different operating strategies during 2013-2019 with Ansoff Matrix along with environmental factors either external or internal that possibly affect the effectiveness of operating strategies. I applied the PEST analysis for analyzing macro-environment factors, Porter’s five forces analysis for investigating environment in the low-cost carrier market, also Nash equilibrium and theory of oligopoly for examining decisions of airlines under changing environmental factors. The result from the study indicated that Thai AirAsia has ticket prices strategy according to consumers’ preference in providing low prices even under the changing of external factors. Also, expansion of its fleet for responding to the growth of demand in the market along with relies on a relationship with AAB or AirAsia Berhad that facilitates Thai AirAsia has effective management and has cost advantages among other low-cost carries in Thailand.